2003
DOI: 10.1063/1.1622790
|View full text |Cite
|
Sign up to set email alerts
|

Observation by photothermal microscopy of increased silica absorption in laser damage induced by gold nanoparticles

Abstract: International audienceIn order to understand laser-induced damage in glass, we subjected engineered SiO2 thin films containing sub-micron gold inclusions to high fluences, and observed the results using several means of analysis. We found decoupling in time between the emission of gold and that of silicon with samples containing gold spheres of diameter 3 nm. We have analyzed the changes in the silica optical absorption at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…8 that there is a very good agreement between experimental and theoretical results (at the set of parameters γ 8 and n 0 5 × 10 6 cm −2 ) at IR irradiation compared to UV irradiation, so the size distribution and density of nano-absorbers can be obtained according to the method. Since the additional absorbing materials generated in pulse duration may have a more significant impact on the damage of fused silica at UV irradiation, there is a little discrepancy between experimental and theoretical results at UV irradiation [27]. The density of nano-absorbers obtained by the method has a good agreement with these results [19,28].…”
Section: Methodsmentioning
confidence: 67%
“…8 that there is a very good agreement between experimental and theoretical results (at the set of parameters γ 8 and n 0 5 × 10 6 cm −2 ) at IR irradiation compared to UV irradiation, so the size distribution and density of nano-absorbers can be obtained according to the method. Since the additional absorbing materials generated in pulse duration may have a more significant impact on the damage of fused silica at UV irradiation, there is a little discrepancy between experimental and theoretical results at UV irradiation [27]. The density of nano-absorbers obtained by the method has a good agreement with these results [19,28].…”
Section: Methodsmentioning
confidence: 67%
“…Therefore, GNPs including nanoparticles, nanoshells, nanorods, nanocages and nanostars have shown the ability to selectively destroy cancer cells by utilizing targeting molecules and NIR heating [74,120,130]. Finally, the optical properties of GNPs have been used to develop microscopy, namely absorption, scattering, polarization and photothermal microscopy [131135]. Finally, the photothermal properties of nanoparticles could potentially be used as a surgical tool in parts of the body considered inaccessible using traditional surgical methods.…”
Section: Photothermal Therapymentioning
confidence: 99%
“…These measurements show a thousandfold increase in absorption when a sharp fluence threshold is exceeded, which indicates that a profound transformation of the silica around inclusions has occurred. 14 In summary, all these studies revealed that the defects induce a change in the silica film, which becomes absorbent and then breaks down because it takes some part of the laser energy. However, it is not yet known if the induced change concerns the atomic or electronic structure of the film.…”
Section: Introductionmentioning
confidence: 97%